20 years of local ecological public health: the experience of Sandwell in the English West Midlands. Issue 10 (October 2015) - Middleton, J.; Saunders, P.
Abstract: A long-term picture of the economy and living conditions of Sandwell, an area of England's industrial Midlands, is presented to explore how these underpin and influence its 'health economy'. Sandwell's experience illustrates how public health actors have to tackle industrial and other factors which shape human health. The paper explores how the ecological public health perspective has helped inform the modern public health task in an area such as Sandwell. Some lessons are offered, including: the need to understand the specific economic legacy of a local area (in Sandwell, principally one of polluting and then declining manufacturing industries); the continuing story of infection control; the complexity of tackling poor diet; and the importance of the built environment and town planning. Faced by such challenges, local public health action represents, in effect, an attempt to transcend unecological public health. This can be exciting, innovative and ultimately successful; but it also means being prepared to face daunting and politically charged obstacles and superior national or international forces over which local public health practitioners conventionally have little leverage. The paper argues that, in such unequal power circumstances, public health practitioners have to draw on the creativity within the local population and build a facilitative alliance of formal and informal pro-public health actors. Despite the confounding odds and ever-present stretched resources, the Sandwell experience gives grounds for optimism, being a story of constant creativity and effective local alliances.